PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERINTEGRASI STEM TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 15 PADANG - Pyo, Debi Ade; Mirna, Mirna (Departemen Matematika, 2024)
Abstract – Students must learn mathematical problem solving, a fundamental cognitive skill and the major purpose of maths. According to observations in class VIII of SMP Negeri 15 Padang, this ability is low. Research used STEM-integrated Problem Based Learning (PBL) to address these issues. The study described the development and examined whether STEM integrated PBL students are better at using it than conventional learners. Research is quasi-experiment with static two-group design. Population: class VIII SMP Negeri 15 Padang students. Research quizzes and posttests. The final hypothesis test at ? = 0.05 yielded ? - ????? < ?, rejecting ?0. This suggests that the STEM integrated PBL methodology improves mathematical problem-solving.Keywords- Mathematics Problem Solving Ability, STEM, Problem Based Learning Models, Conventional Learning Models